Social Networks in an Assisted Living Community: Correlates of Acquaintance and Companionship Ties Among Residents. (4th May 2021) - Mauldin, Rebecca L; Fujimoto, Kayo; Wong, Carin; Herrera, Sarah; Anderson, Keith A
Abstract: Objectives: Social relationships are important for older adults' well-being, including those who live in assisted living (AL) communities. This study explores coresident networks within an AL community and identifies factors associated with residents' social ties. Methods: Acquaintance and companionship networks within the community are described using cross-sectional survey data ( N = 38). We use inferential network statistical methods to estimate parameters for factors associated with residents' acquaintance and companionship ties. Results: Residents reported an average of 10 acquaintances and almost 4 companionships with other residents in the sample. The likelihood a resident had an acquaintance was associated with higher levels of cognitive functioning ( p < .05), higher levels of physical limitations ( p < .01), living in the AL community for a longer time ( p < .01), and less frequent contact with outside family and friends ( p < .05). Acquaintances were more likely between residents who moved in around the same time as each other ( p < .01), lived on the same floor ( p < .001), or had similar levels of physical limitations ( p < .05). Companionships were more likely to be reported by male residents ( p < .05) and residents with higher levels of cognitive functioning ( p < .05) or depressive symptoms ( p < .05). Longtime residents were more popular as companions ( p < .01). Companionships were more likely between residents who lived on the same floor ( p < .001) or were similar in age ( p < .01). Discussion: This research contributes to the literature of older adults' nonkin social relationships by providing detailed descriptions of the acquaintance and companionship networks within an AL community, quantifying correlates of residents' social ties, and distinguishing between acquaintances and companions.